Cystic intestinal duplication-induced secondary intussusception with associated incidental Meckel’s diverticulum in an infant: a case report with literature review - Chuanyang Liu; Chuanyang Liu; Meng Shi; Jinhua Jia; Jinhua Jia; Yuexia Bai; Shengwei Luan; Hongzhen Liu; Hongzhen Liu; Meng Kong; Meng Kong (Frontiers in Surgery)
BackgroundSecondary intussusception in children is associated primarily with organic intestinal pathologies. Intestinal duplication constitutes an uncommon lead point for such cases, while its co-occurrence with an incidentally discovered Meckel's diverticulum represents an exceptionally rare clinical scenario. This report describes an 8-month-old female infant who presented with secondary intussusception initially attributed to a cystic intestinal duplication, with Meckel's diverticulum discovered incidentally during surgical exploration.Case presentationAn 8-month-old female infant was admitted with recurrent vomiting, intermittent fever, and episodes of intense abdominal pain. Abdominal ultrasound revealed ileocolic intussusception and a cystic mass (3.5 cm × 3.0 cm × 3.0 cm) near the ileocecal junction. After unsuccessful air enema reduction, emergency surgery was performed. During the operation, intussusception was found to be caused by cystic intestinal duplication, which acted as the primary lead point. Notably, a separate Meckel's diverticulum (measuring 2.5 cm × 2.0 cm × 1.5 cm in diameter) was discovered incidentally 30 cm proximal to the ileocecal valve on the antimesenteric border of the ileum, demonstrating no pathological connection to the intussusception. Both lesions were surgically removed. Pathological examination confirmed a cystic intestinal duplication and a Meckel's diverticulum containing ectopic gastric tissue. The patient recovered well postoperatively and showed no recurrence of symptoms over a 30-month follow-up period.ConclusionsIn pediatric patients with secondary intussusception caused by enteric duplication, meticulous intraoperative evaluation following successful reduction is critical to identify concurrent intestinal anomalies, including inverted Meckel's diverticulum—a potential lead point for secondary intussusception. This case highlights the incidental discovery of a coexisting Meckel's diverticulum, which was prophylactically excised despite lacking immediate pathological relevance. Systematic exploration combined with tailored resection strategies ensures definitive resolution of intussusception and long-term complication prevention in such rare dual-pathology presentations.